The Phytophthora RXLR Effector Avrblb2 Modulates Plant Immunity by Interfering With Ca2+ Signaling Pathway - Naveed, Zunaira Afzal; Bibi, Shaheen; Ali, Gul Shad (Frontiers in Plant Science, 2019)
In plants, subcellular fluctuations in Ca2+ ion concentration are among the earliest responses to biotic and abiotic stresses. Calmodulin, which is a ubiquitous Ca2+ ion sensor in eukaryotes, plays a major role in translating these Ca2+ signatures to cellular responses by interacting with numerous proteins located in plasma membranes, cytoplasm, organelles and nuclei. In this report, we show that one of the Phytophthora RXLR effector, Avrblb2, interacts with calmodulin at the plasma membrane of the plant cells. Using deletion and single amino acid mutagenesis, we found that calmodulin binds to the effector domain of Avrblb2. In addition, we show that most known homologs of Avrblb2 in three different Phytophthora species interact with different isoforms of calmodulin. Type of amino acids at position 69 in Avrblb2, which determines Rbi-blb2 resistance protein-mediated defense responses, is not involved in the Avrblb2-calmodulin interaction. Using in planta functional analyses, we show that calmodulin binding to Avrblb2 is required for its recognition by Rpi-blb2 to incite hypersensitive response. These findings suggest that Avrblb2 by interacting with calmodulin interfere with plant defense associated Ca2+ signaling in plants.